Comparative of Vocational Education Management Systems in Thailand and Leading Industrial Countries - Uapipattanakul, Chatkul; Phetmalhkul, Theeraphab; Koolnaphadol, Taweesil (Rajapark Journal, 2023)
The objectives of this research are as follows: (1) to compare and study the budget function of the vocational education management system in Thailand and leading industrial countries; (2) to analyze and compare the vocational education administration systems in Thailand and leading industrialized countries according to the components and dimensions. This study was a qualitative research with in-depth interviews and focus groups with a group of policy experts. A group of professionals in the administration of vocational education institutions and entrepreneur group organizations that use vocational education using selection techniques and purposive sampling. The research tools were interview questions and focus group discussions. The results of the research revealed that the important aspects of the vocational education system were as follows: (1) vocational Education Management Policy In every country, there is a common focus which is aiming for learners to continuously learn and develop knowledge and skills through the life long learning approach. (2) the structure of the vocational education system. Thailand has a centralized management model. As for the leading industrialized countries have decentralized management, making the country's development drive outstanding and progressive. (3) vocational course The curriculum should be must in accordance with the policy of education management. And to allow relevant professional organizations to participate in curriculum preparation in order to create a variety and modernity like leading industrial countries; and (4) teacher development should increase the form of development professional skill for teachers to be effective. To enhance the teacher profession to be proud and to support and promote the quality of life in the teaching profession.